Effectiveness of Cranial Electrotherapy Stimulation on Pain Index, Alexithymia, and Chronic Fatigue in Women with Fibromyalgia - Hashemi Keneti, Seyed Hassan; Badelleh Shamoshaki, Mohammad Taghi; Asadi, Javanshir; Mirani, Arasto (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to investigate the effectiveness of cranial electrotherapy stimulation (CES) on pain intensity, alexithymia, and chronic fatigue in women diagnosed with fibromyalgia.Methods and Materials: A quasi-experimental design was employed using a pre-test, post-test, and follow-up format with experimental and control groups. Twenty-four women diagnosed with fibromyalgia who met the inclusion criteria were selected through convenience sampling and randomly assigned to two groups (n = 12 per group). The experimental group received 12 sessions of CES (20 minutes each, twice weekly for six weeks), while the control group was placed on a waiting list. Data were collected using the Mohammadian Pain Questionnaire (1995), Chalder Fatigue Scale (1993), and the Toronto Alexithymia Scale (TAS-20). Statistical analyses included multivariate analysis of covariance (MANCOVA), univariate ANCOVAs, and Bonferroni post hoc tests, conducted using SPSS-22.Findings: Results indicated significant differences between the experimental and control groups in all three outcome variables at post-test, with sustained effects at follow-up. CES significantly reduced pain intensity (F = 6.58, p = 0.01, η² = 0.24), alexithymia (F = 11.15, p = 0.003, η² = 0.34), and chronic fatigue (F = 16.76, p = 0.001, η² = 0.46). Bonferroni post hoc analysis confirmed significant differences between pre-test and post-test scores in the experimental group for all three variables, while changes between post-test and follow-up were not statistically significant, indicating the persistence of treatment effects.Conclusion: Cranial electrotherapy stimulation is an effective, non-invasive intervention for reducing pain, emotional dysregulation, and fatigue in women with fibromyalgia. Its sustained therapeutic effects and potential integration into multidisciplinary care highlight its clinical value in addressing the complex symptomatology of this disorder.